Amino-functionalized magnetic porous organic polymer for the selective removal of toxic cationic dyes from textile wastewater. (25th May 2022) - Taheri, Nazanin; Dinari, Mohammad
Abstract : An amino-functionalized magnetic porous organic polymer (POP) was synthesized through the Friedel–Crafts reaction for selective adsorption of cationic dyes from aqueous solution. Abstract : Porous organic polymers (POPs) with fascinating porous properties are promising candidates for the removal of organic dyes from textile wastewater. In this research work, an amino-functionalized magnetic POP (FC-POP-EDA@Fe3 O4 ) containing accessible binding sites was successfully synthesized in three steps: (1) the Friedel–Crafts reaction between fluorene and cyanuric chloride, (2) fabricating amine-end capped POP using 1, 2-ethylene diamine and (3) magnetization of amino-functionalized POP through fast reduction based on a co-precipitation method. The porosity and crystallinity of the synthesized adsorbent were characterized using the nitrogen adsorption/desorption isotherm and X-ray diffraction patterns, respectively. The results indicated the mesoporous structure of FC-POP-EDA@Fe3 O4 with well-defined crystallinity and a specific surface area of 402.11 m 2 g −1 . The synthesized FC-POP-EDA@Fe3 O4 exhibited superior adsorption toward the cationic dyes in comparison to the anionic ones. This is associated with the POP adsorbent surface charge determined using the zeta potential analysis. In this regard, for the synthesized POP, the maximum adsorption capacities of 379.75, 240.9, 32.13, and 40.28 mg g −1 were obtained for basic red 46, basic blue 41, direct scarlet 4BS and acid naphthol 6B, respectively. According to the results, FC-POP-EDA@Fe3 O4 is a promising adsorbent for the selective removal of cationic dyes from textile wastewater.